Conservation agriculture and livelihoods of smallholder farmers in Central Mozambique - Nkala, P.; Mango, Nelson; Zikhali, Precious (Informa UK Limited, 2011)
This article demonstrates how conservation agriculture impacts smallholder farmers' livelihoods in Mozambique through increased crop productivity and yields, using primary data on smallholder farmers practicing conservation agriculture and others not using this technology from Nhanguo, Pumbuto, and Ruaca in Manica and Sofala provinces. Data analysis employs semiparametric propensity score matching methods. Direct correlations between conservation agriculture, higher productivity and yields; and indirect correlations with changes in household incomes and food security are suggested. Conclusively, systematic targeting of conservation agriculture to different farmer categories, can improve livelihoods, household incomes and food security. We recommend integration of conservation agriculture into the rural development policy framework in Mozambique.